Geometry of the field lines

Two identical point charges + q +q are placed on the x-axis at ± 5 cm \pm 5~\mbox{cm} . As we know, the total electric field produced by the charges is often visualized using field lines. Consider two particular field lines, one from the left charge (Line A) and one from the right (Line B). The tangent vector to Line A is (1,1) when it leaves the left charge and the tangent vector to Line B is (-1,1) when it leaves the right charge. What is the minimum distance d m i n d_{min} in centimeters between these two lines?


The answer is 3.74.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Mark Hennings
Sep 4, 2013

Suppose that the left-hand charge is at the point ( a , 0 ) (-a,0) , and that the right-hand charge is at the point ( a , 0 ) (a,0) . Then the electrostatic potential ϕ \phi at the point P P of the pair of charges is ϕ ( P ) = q 4 π ε 0 ( 1 r 1 + 1 r 2 ) \phi(P) \; = \; \frac{q}{4\pi\varepsilon_0}\Big(\frac{1}{r_1} + \frac{1}{r_2}\Big) where r 1 r_1 is distance of P P from the left-hand particle, and r 2 r_2 is the distance of P P from the right-hand particle. This potential is axially symmetric, and so we can restrict ourselves to considering a two-dimensional problem. Thus E = ϕ = q 4 π ε 0 [ r 1 3 ( x + a y ) + r 2 3 ( x a y ) ] \mathbf{E}\; = \; -\nabla \phi \; = \; \frac{q}{4\pi\varepsilon_0}\Big[r_1^{-3}{x+a \choose y} + r_2^{-3}{x-a \choose y} \Big] and hence the electric field lines are solutions of the differential equation d x r 1 3 ( x + a ) + r 2 3 ( x a ) = d y r 1 3 y + r 2 3 y \frac{dx}{r_1^{-3}(x+a) + r_2^{-3}(x-a)} \; = \; \frac{dy}{r_1^{-3}y + r_2^{-3}y} or [ r 1 3 y d x r 1 3 ( x + a ) d y ] + [ r 2 3 y d x r 2 3 ( x a ) d y ] = 0 \big[r_1^{-3}y\,dx - r_1^{-3}(x+a)\,dy\big] + \big[r_2^{-3}y\,dx - r_2^{-3}(x-a)\,dy\big] \; = \; 0 If we define θ 1 \theta_1 and θ 2 \theta_2 to be the angles that the lines from P P to the left-hand and right-hand charges make with the positive x x -axis, then cos θ 1 = x + a r 1 cos θ 2 = x a r 2 \cos\theta_1 \; = \; \frac{x+a}{r_1} \qquad \cos\theta_2 \; = \; \frac{x-a}{r_2} and hence it can be shown that sin θ 1 d θ 1 = y [ y d x ( x + a ) d y ] r 1 3 sin θ 2 d θ 2 = y [ y d x ( x a ) d y ] r 2 3 \begin{array}{rcl} -\sin\theta_1\,d\theta_1 & = & y[y\,dx - (x+a)\,dy]r_1^{-3} \\ -\sin\theta_2\,d\theta_2 & = & y\big[y\,dx - (x-a)\,dy]r_2^{-3} \end{array} and hence the general equation of an electric field line is cos θ 1 + cos θ 2 = c \cos\theta_1 + \cos\theta_2 \; = \; c For line A A , we have θ 1 α \theta_1 \to \alpha and θ 2 π \theta_2 \to \pi as P P approaches the left-hand charge, where α = 1 4 π \alpha=\tfrac14\pi . Similarly, for the line B B we have θ 1 0 \theta_1 \to 0 and θ 2 π α \theta_2 \to \pi-\alpha as P P approaches the right-hand charge. Thus the equations of the two lines are cos θ 1 + cos θ 2 = cos α 1 cos θ 1 + cos θ 2 = 1 cos α \cos\theta_1 + \cos\theta_2 \; = \; \cos\alpha-1 \qquad \qquad \cos\theta_1 + \cos\theta_2 \; = \; 1 - \cos\alpha It is clear that lines A A and B B are mirror images of each other in the central line x = 0 x=0 . Thus the smallest distance d d between them is equal to 2 x m i n 2x_\mathrm{min} , where x m i n x_{\mathrm{min}} is the least positive value of x x attained on the line B B .

At the point x = x m i n x=x_\mathrm{min} , we have d x d y = 0 \tfrac{dx}{dy} = 0 , and hence ( x + a ) r 1 3 + ( x a ) r 2 3 = 0 (x+a)r_1^{-3} + (x-a)r_2^{-3} = 0 . Thus we need to solve the simultaneous equations cos θ 1 + cos θ 2 = 1 cos α r 1 2 cos θ 1 + r 2 2 cos θ 2 = 0 \cos\theta_1 + \cos\theta_2 \; = \; 1 - \cos\alpha \qquad \qquad r_1^{-2}\cos\theta_1 + r_2^{-2}\cos\theta_2 \; = \; 0 Multiplying the second by y 2 = r 1 2 sin 2 θ 1 = r 2 2 sin 2 θ 2 y^2\,=\,r_1^2\sin^2\theta_1\,=\,r_2^2\sin^2\theta_2 , we deduce that 0 = sin 2 θ 1 cos θ 1 + sin 2 θ 2 cos θ 2 = cos θ 1 + cos θ 2 cos 3 θ 1 cos 3 θ 2 = ( cos θ 1 + cos θ 2 ) ( 1 cos 2 θ 1 + cos θ 1 cos θ 2 cos 2 θ 2 ) = ( cos θ 1 + cos θ 2 ) [ 1 ( cos θ 1 + cos θ 2 ) 2 + 3 cos θ 1 cos θ 2 ] \begin{array}{rcl} 0 & = & \sin^2\theta_1\cos\theta_1 + \sin^2\theta_2\cos\theta_2\\ & = & \cos\theta_1+\cos\theta_2 - \cos^3\theta_1-\cos^3\theta_2 \\ & = & (\cos\theta_1 + \cos\theta_2)(1 - \cos^2\theta_1 + \cos\theta_1\cos\theta_2 - \cos^2\theta_2) \\ & = & (\cos\theta_1 + \cos\theta_2)\big[1 - (\cos\theta_1+\cos\theta_2)^2 + 3\cos\theta_1\cos\theta_2\big] \end{array} Hence 3 cos θ 1 cos θ 2 = ( 1 cos α ) 2 1 = 4 sin 4 1 2 α 1 3\cos\theta_1\cos\theta_2 \,=\, (1-\cos\alpha)^2-1 \,=\,4\sin^4\tfrac12\alpha - 1 . Thus $\cos\theta_1) and cos θ 2 \cos\theta_2 are the roots of the quadratic 3 X 2 6 sin 2 1 2 α X + 4 sin 4 1 2 α 1 = 0 3X^2 - 6\sin^2\tfrac12\alpha \,X + 4\sin^4\tfrac12\alpha - 1 \; = \; 0 with cos θ 1 > 0 > cos θ 2 \cos\theta_1 > 0 > \cos\theta_2 . For these values of θ 1 \theta_1 and θ 2 \theta_2 we have r 1 cos θ 1 r 2 cos θ 2 = 2 a r 1 sin θ 1 = r 2 sin θ 2 r_1\cos\theta_1 - r_2\cos\theta_2 \,=\,2a\qquad \qquad r_1\sin\theta_1 \,=\,r_2\sin\theta_2 and hence r 1 = 2 a sin θ 2 sin ( θ 2 θ 1 ) r_1 \; = \; \frac{2a \sin\theta_2}{\sin(\theta_2-\theta_1)} and thus x m i n = r 1 cos θ 1 a = 2 a cos θ 1 sin θ 2 sin ( θ 2 θ 1 ) a x_{\mathrm{min}}\; = \; r_1\cos\theta_1 - a \; = \; \frac{2a \cos\theta_1\sin\theta_2}{\sin(\theta_2-\theta_1)} - a With α = 1 4 π \alpha = \tfrac14\pi and a = 5 a=5 , we obtain d = 2 x m i n = 3.743 d \; = \; 2x_\mathrm{min} \; = \; 3.743

that's amazing but a little bit complicated

Xuan Hien Bui - 7 years, 9 months ago

Log in to reply

Well possibly, but deriving the formulae for the field lines is essentially bookwork (if you have the right sort of book!), and is very easy to generalise, so we could use this method to answer questions with different charges at the two points.

Mark Hennings - 7 years, 9 months ago

Log in to reply

could you recommend any specialised materials about magnetic and field lines? thanks so much

Xuan Hien Bui - 7 years, 9 months ago

Log in to reply

@Xuan Hien Bui My "book" is more like a collection of books. From the EM point of view, you need a book which is aimed at studying Mathematical Physics rather than Physics; in other words, it sets out to investigate solutions of the Maxwell equations from a rigorous point of view. The ones I use are all quite old now (as am I), and are not readily available. I cut my teeth on one by Clemmow. You also need a good supply of techniques on handling the calculus of vector-valued functions: Bourne & Kendall's "Vector Calculus and Cartesian Tensors" is one to look at, but there are plenty of others. Otherwise, books on solving complex differential equations, orthogonal trajectories, etc. are all useful.

Mark Hennings - 7 years, 9 months ago

I too would like to know about the book. Can you please post the name of the book?

Pranav Arora - 7 years, 9 months ago

Very well done and thanks for taking time to post a well written solution.

Ganesh Sundaram - 7 years, 9 months ago
Jatin Yadav
Sep 1, 2013

d d will be min when electric field line is perpendicular to x axis.

Let the distance along axis of the point from the left charge where this happens be x and the y - coordinate be y.

Now let us consider a circle tangent to this field line passing through this point and another such point in downward direction having its plane along Y-Z plane. Let us consider another such circle at the beginning of the field line tangent to it and very close to x = 5 x = -5 and in Y-Z plane.

Flux through both the circles must be equal.

q 2 0 [ 1 1 2 ] = q 2 0 [ [ 1 x x 2 + y 2 ] [ 1 ( d x ) ( d x ) 2 + y 2 ] ] \Rightarrow \frac{q}{2 \in_{0}}[ 1 - \frac{1}{\sqrt{2}}] = \frac{q}{2 \in_{0}}[ [1 - \frac{x}{\sqrt{x^2 + y^2}} ] - [ 1- \frac{(d - x)}{\sqrt{(d - x)^2 + y^2}}]]

( d x ) ( d x ) 2 + y 2 x x 2 + y 2 = 1 1 2 . . . . . . ( i ) \Rightarrow \frac{(d - x)}{\sqrt{(d - x)^2 + y^2}} - \frac{x}{\sqrt{x^2 + y^2}} = 1 - \frac{1}{\sqrt{2}} ...... (i)

Now , E x E_{x} = 0 at this point.Hence E x E_{x} of both charges will cancel.

k q x 2 + y 2 x x 2 + y 2 = k q ( 10 x ) 2 + y 2 ( 10 x ) ( 10 ) x 2 + y 2 . . . . . . ( i i ) \Rightarrow \frac{kq}{x^2 + y^2}\frac{x}{\sqrt{x^2 + y^2}} = \frac{kq}{(10 - x)^2 + y^2}\frac{(10 - x)}{\sqrt{(10 - )x^2 + y^2}} ...... (ii)

Solving ( i ) (i) and ( i i ) (ii) , we get

x = 3.13 x = \fbox{3.13} and y = 6.67 y= \fbox{6.67}

Hence , d m i n = 10 2 ( 3.13 ) = 3.74 d_{min} = 10 - 2*(3.13) = \fbox{3.74} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...